Noninvasive assessment of liver fibrosis and its clinical significance in nonalcoholic fatty liver disease. Issue 6 (12th April 2022) - Tamaki, Nobuharu; Kurosaki, Masayuki; Huang, Daniel Q.; Loomba, Rohit
Abstract: Liver fibrosis is the most important prognostic factor in patients with nonalcoholic fatty liver disease (NAFLD). Several noninvasive markers for fibrosis, including blood‐based markers and imaging based‐markers have been developed. Indirect fibrosis markers (e.g., fibrosis‐4 index and NAFLD fibrosis score) consist of standard laboratory data and clinical parameters. Given its availability and high negative predictive value for advanced fibrosis, these markers are suitable for screening at primary care. Blood‐based fibrogenesis markers (enhanced liver fibrosis and N‐terminal propeptide of type 3 collagen), ultrasound‐based modalities (vibration‐controlled transient elastography, point shear wave elastography [SWE], and two‐dimensional SWE), and magnetic resonance elastography have high diagnostic accuracy for liver fibrosis and are suitable for diagnosing liver fibrosis at secondary care centers. Sequential use of these markers can increase diagnostic accuracy and reduce health care costs. Furthermore, combining noninvasive makers may assist in identifying candidates for pharmacological trials and reducing screening failure. Emerging data suggest that these noninvasive markers are associated with liver‐related events (hepatocellular carcinoma and decompensation) and mortality. Furthermore, delta change in noninvasive markers over time is also associated with time‐course change in fibrosis, liver‐related event risk, and mortality risk. However, the association between liver fibrosis and cardiovascular disease (CVD) risk is still controversial. CVD risk may decrease in patients with decompensated liver disease and noninvasive markers may be useful for assessing CVD risk in these patients. Therefore, noninvasive markers may be utilized as measures of fibrosis as well as real‐time prognostic tools, in place of liver biopsy.